STRATEGI MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI YAYASAN PERGURUAN SMP AL-HIDAYAH MEDAN - Hanafi, Yusron; Fatimah, Laila (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2021)
This research was conducted at the Al-Hidayah Middle School Foundation, Medan Tembung, this type of research is a qualitative research. The approach in this study uses a descriptive qualitative approach. As informants in this study were principals, vice principals, teachers, staff and students. Collecting data using the method of Observation, Interview and Documentation. Data analysis was carried out by means of data reduction, data presentation and conclusion drawing. The purpose of this research. 1) knowing how to plan, 2) organizing, 3) implementing, 4) supervising and constraining the principal's management process in improving student achievement at the Al-Hidayah Middle School Foundation, Medan Tembung. The results showed that: the implementation of the principal's management function in improving student achievement at the Al-Hidayah Middle School Foundation, Medan Tembung, was to use planning, organizing, actuating, controlling (POAC). The planning made by the principal is divided into two, namely: planning for students from making lesson plans and extracurricular activities. While planning for teachers to make coaching and guidance. Then the organization carried out by the principal is to create all stakeholders into one good forum. Then the principal implements or moves a good container. Then the principal implements or moves the test container to work together in building the school's vision, mission and goals. While the last is how the principal evaluates and assesses the entire program implemented.